In view of standardization: comparison and analysis of initial management of severely burned patients in Germany, Austria and Switzerland - Münzberg, Matthias; Fischer, Sebastian; Wölfl, Christoph Georg; Grützner, Paul Alfred; Kremer, Thomas; Kneser, Ulrich; Hirche, Christoph (Burns, 2015)
Introduction - Initial treatment of severely injured patients in German speaking trauma centers follows precise sequences. Several guidelines and training courses ensure a constant quality in providing evidence-based treatment for these patients. Similar standards, algorithms and guidelines for the treatment of severely burned patients are lacking. This raises the question about the current standard of care for burn victims in German speaking burn centers. In order to achieve standardization, as a first step this study surveys principles of burn room organization and management in these burn centers. - Material and methods - A questionnaire including 40 questions regarding burn room organization, personnel structure and qualification, infrastructural conditions and quality management was developed and sent to 21 level one burn centers in Germany, Austria and Switzerland. - Results - The rate of returned questionnaires was 81%. The analysis revealed varying personnel and infrastructural conditions in participating burn centers. Indications for admission to the burn room and admission procedures itself are different throughout surveyed hospitals. Individual standard operating procedure (SOP) for burn trauma admissions was available in most burn centers and nearly all participants register their burn trauma cases using an in-house burn register. - Conclusion - The survey suggests a lack of standardization in personnel structure, infrastructure and treatment approach for the initial clinical care of severely burned patients in burn centers across the German speaking countries. Further evaluation of existing protocols and international standards in burn care is inevitable to develop standardized guidelines for burn care and to improve quality of care.